2019
DOI: 10.1177/1044389419847326
|View full text |Cite
|
Sign up to set email alerts
|

Remaining in Foster Care After Age 18 and Youth Outcomes at the Transition to Adulthood: A Review

Abstract: Many foster youth do not exit care for a permanency option and remain in foster care until they age out or are emancipated. Research findings have described the alarming circumstances of these former foster children’s adaptation to emerging adulthood. Public policy over the past three decades has sought various means of improving outcomes for these former foster youth. This review examines the legislative history leading up to extended care, the research on youth leaving foster care, youth preferences for exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 57 publications
(79 reference statements)
1
15
0
1
Order By: Relevance
“…Over the past decade, much research has been conducted in relation to care leaving and the transition to adulthood (e.g. Jones, 2019;Mendes & Snow, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, much research has been conducted in relation to care leaving and the transition to adulthood (e.g. Jones, 2019;Mendes & Snow, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom (UK), care leavers experience an 'accelerated and compressed' journey to adulthood compared with their non-looked after peers for whom transition is more gradual and ongoing support from key adult figures in their lives is more likely to be available (Jones, 2019;Mendes and Rogers, 2020;Stein, 2006Stein, , 2012. Many young people leaving care are likely to experience multiple and bewildering transitions that evoke feelings of instability, powerlessness, unpreparedness, abandonment and mistrust (Butterworth et al, 2017;Stein, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Young people transitioning from out-of-home care (OOHC), often called care leavers or care experienced young people, are recognized universally as a vulnerable group who have generally not received the ongoing and holistic support that they require to transition successfully into adult life. Numerous research studies have reported common concerns around poor outcomes in relation to housing, health, education, training and employment, and other core development needs (Jones, 2019;Mann-Feder and Goyette, 2019;Stein and Munro, 2008;Stott, 2013;Woodgate et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, most leave care at 18 years old or even younger, and do not receive the ongoing financial, social and emotional support and nurturing offered by most families of origin up to and even well beyond 25 years of age. In fact, many abruptly lose their limited existing supports from carers and other community connections whilst being expected to move rapidly to independent living (Jones, 2019). These 'accelerated and compressed transitions' to adulthood make it difficult for them to access mainstream educational, employment, housing, health and other development and transitional pathways (Stein, 2016: v).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation